O Espírito do Senhor atua a partir de baixo: a pneumatologia de Victor Codina. - Silva, Tiago Santos da (2021)
Our work aims to present a synthesis of the pneumatology of Victor Codina, elaborated from Latin America, in which the author states that “the Spirit of the Lord works from below”. The research was developed from the author's personal experience and theological production, and using a narrative and symbolic methodology, giving the text a more pastoral sense. We worked on the theobiographical traces of the author, that is, the path he took until deepening pneumatology. Followed by the structure of his theology of the Holy Spirit, in which he emphasizes the action of the Spirit in the subject, in the ecclesial community and in the cosmos. He takes a path integrating Christology and pneumatology with an emphasis on ecclesiology, emphasizing that the Spirit has no other message than that of Jesus, but is memory, updating and consummation of his life and work. Realize the pneumatological deficit, and especially with regard to the relationship of the Spirit and the poor. Its elaboration aims to contemplate the data of the original cultures and the content of the Christian Revelation. It also makes a resumption of the movements of the Spirit in history. This acting from the insignificant and in function of them. He acts in the Church, making her an instrument of the Kingdom in the unity of plurality. The criterion for discerning the presence of the Holy Spirit in people, groups, movements, communities, religions and cultures is the confrontation with the life of Jesus of Nazareth and his project. We must listen to God where life cries out, because it is the cry of the creative, life-giving and sanctifying Spirit. The outcry is felt especially from below, situations of injustice, chaos, violence. It is with a view to taking care of this dimension that its pneumatological proposal goes through the personal, the ecclesial and the historical-cosmic. Divine Ruah makes us a being in the relationship and in the use of conscience, constitutes ecclesial synodality and spreads throughout the world, leading all creation to cosmic integration. The author thus leaves us with the task of deepening pneumatology even further from the perspective of the poor, leading to theology, spirituality and evangelization.